Characterization of the Anxiolytic Activity of Nunavik Rhodiola rosea - Cayer, Christian; Ahmed, Fida; Filion, Vicky; Saleem, Ammar; Cuerrier, Alain; Allard, Marc; Rochefort, Guy; Merali, Zul; Arnason, John T. (Planta Medica, 2013)
Rhodiola rosea is a medicinal plant used by the indigenous Inuit people of Nunavik and Nunatsiavut, Eastern Canada, as a mental and physical rejuvenating agent. This traditional use led to the present investigation of R. rosea in the context of anxiety disorders. An alcohol extract of R. rosea roots was characterized phytochemically and orally administered for three consecutive days to Sprague-Dawley rats at 8 mg/kg, 25 mg/kg, and 75 mg/kg body weight. The rats were subjected to three behavioral paradigms of anxiety, including the elevated plus maze, social interaction, and contextual conditioned emotional response tests. Rhodiola rosea showed dose-dependent anxiolytic activity in the elevated plus maze and conditioned emotional response tests, with moderate effects in the higher-anxiety SI test. The active dose varied according to the anxiety test. In order to elucidate a mechanism, the extract was further tested in an in vitro GABAA-benzodiazepine receptor-binding assay, where it demonstrated low activity. This study provides the first comparative assessment of the anxiolytic activity of Nunavik R. rosea in several behaviour models and suggests that anxiolytic effects may be primarily mediated via pathways other than the GABAA-benzodiazepine site of the GABAA receptor.
Keywords: Rhodiola rosea; Crassulaceae; anxiolytic; elevated plus maze; social interaction; conditioned emotional response; GABAA-benzodiazepine receptor